Market-led Extension and Empowerment of Smallholder Vegetable Farmers in India - K. C., Shinogi; Krishnankutty, Jayasree; S, Krishnan; Srivastava, Sanjay; Gills, Reshma; Balakrishnan, Renu (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted to analyze the impact of market-led extension in the marketing pattern and empowerment of smallholder farmers of India. Since market-led extension activities mostly implemented through self help groups (SHGs) 60 marginal vegetable farmers with SHG membership and another 60 marginal vegetable farmers with no SHG membership selected as the respondents. Results conveyed that SHG farmers marketed vegetables mainly through farmers’ markets. But, majority of the non-SHG farmers sold vegetables through commission agents. Empowerment analysis done using the criteria of ≥75% of maximum attainable score showed significant differences between the empowerment status of SHG and non-SHG farmers. About 62% of SHG farmers found empowered because of their participation in SHGs whereas very few (2%) of the non-SHG farmers showed empowerment. It was also found that social recognition is the prime variable influenced the empowerment of SHG farmers followed by income generation. Though only a few non-SHG farmers showed empowerment again social recognition identified as the major variable contributed to their empowerment score followed by innovativeness. Since social recognition played prime role in the empowerment process of both SHG and non-SHG farmers it could be considered as the precursor of empowerment process. It is evident from the study that in order to convert social recognition to empowerment a reasonable level of income generation is also necessary. To extend the benefits of market-led extension to more rural farmers the technology dissemination system should also be improved by incorporating those grass root level organizations (public/private) working among them.